Nano-fluid for imbibition and oil discharge of low-permeability reservoir and preparation method of nano-fluid

By using nanofluids composed of parental modified nanoSiO2 particles and bimini surfactant in low-permeability reservoirs, the problem of low-permeability reservoirs is solved in the process of water injection development, and the efficient permeability and oil dissipation effect under high temperature and high salt conditions is achieved.

CN119899652APending Publication Date: 2025-04-29CHINA NATIONAL OFFSHORE OIL (CHINA) CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510062143.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Low permeability oil reservoirs are inefficient during water injection development, and have problems such as flooding, decreasing formation energy, and inability to flow crude oil in the retention layer, making it difficult to achieve good mining results.

Method used

A nanofluid for infiltration and oil discharge in low permeability reservoirs is developed, including amphiphilic modified nanoSiO2 particles and a bimini surfactant, which can exert infiltration and oil discharging under high temperature and high salt conditions.

Benefits of technology

Under high temperature and high salt conditions, this nanofluid can effectively improve the oil permeability and oil disposal efficiency of the reservoir, improve recovery rate, and have good temperature and salt resistance. It is suitable for environments where the reservoir temperature is ≥160℃, mineralization degree ≥30,000mg/L, and permeability ≤50×10-3μm2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a nanofluid for imbibition and oil discharge of a low-permeability reservoir and a preparation method of the nanofluid. The nanofluid for imbibition and oil discharge of the low-permeability reservoir is prepared from the following components in percentage by mass: 0.01 to 0.03 percent of amphiphilic modified nano SiO2 particles, 0.20 to 0.40 percent of gemini surfactant and the balance of simulated seawater. The invention provides a preparation method of a nanofluid for imbibition and oil discharge of a low-permeability reservoir, which comprises the following steps: adding a gemini surfactant into simulated seawater, stirring for 30-100 minutes, uniformly mixing, adding amphiphilic modified nano SiO2 particles, stirring for 10-60 minutes, and uniformly mixing to obtain the nanofluid. The preparation method is simple, easy to operate and simple in reaction condition, and can be used on an oil field on a large scale; after the nanofluid is injected into a stratum, the nanofluid for imbibition and oil discharge of the low-permeability reservoir generates a wedge-shaped film in a contact area of rock and oil, the structure can generate forward thrust, and the oil can be possibly stripped from the surface of the rock in combination with auxiliary effects of reducing interfacial tension, reversing wettability and the like generated by a system, so that the aim of improving the recovery ratio is fulfilled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nanofluid for oil imbibition and drainage in a low-permeability oil reservoir and a preparation method thereof, belonging to the technical field of oilfield chemicals. Background Art

[0002] As most of my country's oilfield development stages have reached the middle and late stages, the need to improve the recovery rate of crude oil in low-permeability reservoirs has become increasingly prominent. The large-scale development of conventional oil reservoirs has led to a sharp decline in recoverable reserves year by year. The exploration, development and utilization of low-permeability reservoirs are of great significance to ensuring the sustainable development of my country's oil and gas industry.

[0003] At present, water injection is often used to exploit low permeability oil reservoirs. However, due to the low porosity, low permeability and strong heterogeneity of these reservoirs, the efficiency of water injection is generally low. In addition, water injection often leads to problems such as water flooding, rapid formation energy decline, water accumulation around the injection wells, and the inability of crude oil in the retention layer to flow, thus failing to achieve good exploitation results.

[0004] A large number of indoor research and development practices have shown that for low-permeability reservoirs, under the action of capillary force, crude oil can gradually converge from pores with smaller pore sizes to large pores, ultimately achieving oil-water replacement and increasing single-well production and recovery. Therefore, giving full play to the capillary force of imbibition can become an effective development method for this type of reservoir. However, the oil reservoirs in the western South China Sea are currently high in temperature and mineralization, and are high-temperature and high-salt reservoirs. Therefore, the development of an efficient, temperature-resistant and salt-resistant nano-imbibition oil-displacing agent is of great significance. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a nanofluid for oil drainage in low permeability reservoirs, which can achieve the following conditions: temperature ≥160°C, mineralization ≥30000mg / L, permeability ≤50×10 -3 μm 2 It can still synergistically play an excellent role in imbibition and oil recovery in the strata.

[0006] The nanofluid for oil drainage in low permeability reservoirs provided by the present invention has the following mass fraction composition:

[0007] 0.01% to 0.03% of amphiphilic modified nano-SiO2 particles, 0.20% to 0.40% of Gemini surfactant, and the rest of simulated seawater.

[0008] Wherein, the structure of the amphiphilic modified nano-SiO2 particles is as follows:

[0009]

[0010] The preparation method of the amphiphilic modified nano-SiO2 particles is as follows:

[0011] S1, adding hydrophilic nano-SiO2 particles and solid paraffin to an aqueous solution of didodecyl dimethyl ammonium bromide, emulsifying and cooling to obtain paraffin microspheres;

[0012] S2, adding the paraffin microspheres and 3-mercaptophenylpropyltriethoxysilane to ethanol and stirring, then adding hydrogen peroxide, continuing to stir and filter, and after removing the paraffin, obtaining nano-SiO2 particles functionalized with a portion of benzenesulfonic acid groups;

[0013] S3, adding the nano-SiO2 particles functionalized with some benzenesulfonic acid groups into a solution of n-octyltriethoxysilane, and obtaining the amphiphilic modified nano-SiO2 particles through reaction.

[0014] Wherein, in step S1, the mass ratio of the hydrophilic nano-SiO2 particles, the solid paraffin and the didodecyl dimethyl ammonium bromide is 1:5-24:0-0.25;

[0015] Wherein, in step S2, the mass ratio of the 3-mercaptophenylpropyltriethoxysilane to the paraffin microspheres is 1:1-10, and the stirring time after adding the hydrogen peroxide is 4-24 hours.

[0016] Wherein, in step S3, the mass ratio of the n-octyltriethoxysilane to the partially benzenesulfonic acid functionalized nano-SiO2 particles is 1:0.8-3;

[0017] The reaction temperature is 25-55°C and the reaction time is 4-6h.

[0018] The structural formula of the Gemini surfactant is as follows:

[0019]

[0020] The preparation method of the gemini surfactant comprises the following steps:

[0021] Sa, dodecyl alcohol polyoxyethylene ether and thionyl chloride react to obtain yellow crystal A;

[0022] Sb, in the presence of potassium carbonate, ethylenediamine and sodium 2-bromoethylsulfonate react to obtain a white solid B;

[0023] Sc. In the presence of potassium carbonate, the yellow crystal A reacts with the white solid B to obtain the product.

[0024] The salinity of the simulated seawater may be 30,000 mg / L to 50,000 mg / L.

[0025] The present invention further provides a method for preparing the nanofluid for oil drainage in low permeability reservoirs, comprising the following steps:

[0026] The gemini surfactant is added to the simulated seawater, stirred for 30 to 100 minutes, and after being evenly mixed, the amphiphilic modified nano-SiO2 particles are added, stirred for 10 to 60 minutes, and mixed evenly to obtain the product.

[0027] Compared with the prior art, the advantages and positive effects of the present invention are:

[0028] (1) The preparation method is simple, easy to operate, and the reaction conditions are simple, and it can be used on a large scale in oil fields.

[0029] (2) After injection into the formation, the nanofluid used for oil drainage in the low permeability reservoir produces a wedge-shaped film in the contact area between the rock and the oil. This structure will generate a forward thrust. Combined with the auxiliary effects of the system such as reducing interfacial tension and wettability reversal, it is possible to strip the oil from the rock surface and achieve the purpose of improving the recovery rate.

[0030] (3) The nanofluid for oil drainage in low permeability reservoirs has good temperature and salt resistance and can be used in reservoirs with a temperature of ≥160°C, a mineralization of ≥30000 mg / L, and a permeability of ≤50×10 -3 μm 2 conditions. DETAILED DESCRIPTION

[0031] The present invention is further defined below in conjunction with the description and examples, but is not limited thereto.

[0032] In the following examples, the amphiphilic modified nano-SiO2 particles were prepared as follows:

[0033] First, 0.5g of didodecyl dimethyl ammonium bromide was dissolved in 50mL of distilled water. Then, 2g of hydrophilic nano-SiO2 particles and 10g of solid paraffin were placed in the beaker containing 50mL of didodecyl dimethyl ammonium bromide solution, and emulsified for 5min at 80℃ and 12000r / min using FJ300-SH digital high-speed dispersing homogenizer. After the emulsification, the emulsion was immediately placed in the refrigerator to cool so that the paraffin microspheres were completely solidified, and the surface of the paraffin microspheres was repeatedly rinsed with deionized water to remove the hydrophilic nano-SiO2 particles loosely adsorbed on the surface of the paraffin.

[0034] Then the paraffin microspheres were placed in a 25°C drying oven and vacuum dried for 12 hours. 5 g of dried paraffin microspheres and 0.5 g of 3-mercaptophenylpropyltriethoxysilane were placed in a round-bottom flask containing 50 mL of anhydrous ethanol and stirred at room temperature using a magnetic stirrer for 4 hours. After stirring, 2 mL of hydrogen peroxide was added dropwise, and stirring was continued for 24 hours. After filtering out the paraffin microspheres, the paraffin was dissolved with chloroform, and the partially benzenesulfonic acid functionalized nano-SiO2 particles were obtained by centrifugation (speed 3000 r / min), and then placed in a vacuum drying oven at 80°C for 12 hours.

[0035] 0.3 g of n-octyl triethoxysilane was added to 50 mL of anhydrous ethanol, and after stirring for 48 h, 1 g of partially benzenesulfonic acid functionalized nano-SiO2 particles was added and reacted at room temperature for 4 h. After the reaction, the solid particles were filtered out, and then the surface of the solid particles was washed with anhydrous ethanol to remove the unreacted n-octyl triethoxysilane, and the white powdery amphiphilic nano-SiO2 particles were collected by centrifugation.

[0036] The structure of the amphiphilic nano-SiO2 particles used in the present invention is shown in the following formula (1-hydrophobic group (octyl group); 2-hydrophilic group (benzenesulfonic acid group)):

[0037]

[0038] The structure of the Gemini surfactant used in the following examples is shown in the following formula, wherein x is 2 to 16, y is 3 to 15, and z is 2 to 6:

[0039]

[0040] The synthesis method of Gemini surfactants is as follows:

[0041] Take 20-50g of dodecyl alcohol polyoxyethylene ether in a single-necked flask, add 15-60mL of chloroform as solvent, heat to 35-60℃, slowly drop 5-20mL of thionyl chloride, react for 1-5h, and distill under reduced pressure to obtain the product as yellow crystal A. Take 1-2g of ethylenediamine and 5-10g of potassium carbonate and place them in a single-necked flask, add 30-60mL of acetone / water mixed solution with a certain volume ratio as solvent to ethanol / water mixed solution (1:1) to dissolve, stir and dissolve, heat to 30-60℃, slowly drop 10-20g of sodium 2-bromoethylsulfonate dissolved in 30mL of mixed solution, react for 5-20h (30-60℃), stop the reaction, and distill under reduced pressure to obtain white solid B. 30-50g of yellow crystal A and 5-10g of potassium carbonate are placed in a single-necked flask, and a mixed solution of acetone / water in a certain volume ratio is used as a solvent. After stirring and dissolving, the temperature is raised to 50-100°C, and 5-10g of white solid B dissolved in 30mL of the mixed solution is slowly added dropwise. After the addition is completed, the reaction is stirred at 50-100°C for 8-15h. After the reaction is completed, the solvent is removed by distillation under reduced pressure, ethanol is added, and impurities are removed by filtration to obtain a colorless transparent liquid. The ethanol is removed under reduced pressure to obtain the gemini surfactant GAES.

[0042] Embodiment 1,

[0043] Prepare simulated seawater with a mineralization degree of 30,000 mg / L, stir for 20 minutes to completely dissolve it; add 0.20 wt% of gemini surfactant to the prepared simulated seawater, stir for 30 minutes, mix evenly, then add 0.01% of amphiphilic modified nano-SiO2 particles, stir for 20 minutes, mix evenly, and obtain a nano-infiltration enhancement system.

[0044] Comparative Example 1

[0045] Prepare simulated seawater with a mineralization degree of 30,000 mg / L, stir for 20 minutes to completely dissolve it; add 0.20 wt% of gemini surfactant to the prepared simulated seawater, stir for 30 minutes, mix evenly, then add 0.1% of amphiphilic modified nano-SiO2 particles, stir for 20 minutes, mix evenly, and obtain a nano-infiltration enhancement system.

[0046] Comparative Example 2

[0047] Prepare simulated seawater with a mineralization degree of 30000 mg / L, stir for 20 minutes to completely dissolve it; add 0.20 wt% of Gemini surfactant to the prepared simulated seawater, stir for 30 minutes, mix evenly, and obtain a nano-infiltration enhancement system.

[0048] Comparative Example 3

[0049] Prepare simulated seawater with a mineralization of 30,000 mg / L, stir for 20 minutes to completely dissolve it; add 0.20 wt% of cationic gemini surfactant PF-CGS (Tianjin COSL Chemical Co., Ltd.) to the prepared simulated seawater, stir for 30 minutes, mix evenly, then add 0.02% of amphiphilic modified nano-SiO2 particles, stir for 20 minutes, mix evenly, and obtain a nano-infiltration enhancement system.

[0050] Comparative Example 4

[0051] Prepare simulated seawater with a mineralization of 30,000 mg / L, stir for 20 minutes to completely dissolve it; add 0.20 wt% nonionic-anionic gemini surfactant FOS (Tianjin Youlian Petrochemical Co., Ltd.) to the prepared simulated seawater, stir for 30 minutes, mix evenly, then add 0.02% amphiphilic modified nano-SiO2 particles, stir for 20 minutes, mix evenly, and obtain a nano-infiltration enhancement system.

[0052] Embodiment 2,

[0053] Prepare simulated seawater with a mineralization degree of 30,000 mg / L, stir for 20 minutes to completely dissolve it; add 0.20 wt% of gemini surfactant to the prepared simulated seawater, stir for 30 minutes, mix evenly, then add 0.02% of amphiphilic modified nano-SiO2 particles, stir for 20 minutes, mix evenly, and obtain a nano-infiltration enhancement system.

[0054] Embodiment 3,

[0055] Prepare simulated seawater with a mineralization degree of 30,000 mg / L, stir for 20 minutes to completely dissolve it; add 0.20 wt% of gemini surfactant to the prepared simulated seawater, stir for 30 minutes, mix evenly, then add 0.03% of amphiphilic modified nano-SiO2 particles, stir for 20 minutes, mix evenly, and obtain a nano-infiltration enhancement system.

[0056] Example 4: Experiment on evaluation of wettability

[0057] The measurement was carried out according to the contact angle method of standard SYT 5153-2017 “Method for determination of wettability of reservoir rocks”.

[0058] ① Soak the quartz glass sheet in aging oil, then put it in a 60℃ constant temperature water bath, take it out after aging for 2 days, and test the water phase wetting angle;

[0059] ② After the above quartz plate is immersed in 0.3% osmotic agent solution for 2 days, the water phase wetting angle is tested, and the difference between the two is the wetting angle change value. See Table 1 below.

[0060] Table 1 Wetting angle measurement results

[0061]

[0062]

[0063] It can be seen from the data in Table 1 that the nanofluids containing amphiphilic nanoparticles and gemini surfactants change the rock wettability better than the nanofluids containing only gemini surfactants, and the wetting reversal ability of the nanofluids with GAES as the gemini surfactant is better than the nanofluids with PF-CGS and FOS as the gemini surfactant.

[0064] Example 5: Capillary self-priming height evaluation experiment

[0065] (1) Preparation of lipophilic capillaries

[0066] ① The capillary was ultrasonically treated with carbon tetrachloride and acetone:ethanol = 1:1 (volume ratio) for 40 min to remove organic matter on the surface;

[0067] ②Use dilute hydrochloric acid solution (1:10) to roughen and activate the capillary surface for 20 minutes; use deionized water to perform ultrasonic cleaning to remove residual acid until pH>6.5, and then dry at 105°C;

[0068] ③ Prepare aging oil in proportion, the aging oil composition is crude oil: aviation kerosene = 2:5. Completely immerse the treated capillary in the crude oil and age it at 60°C for 3 days;

[0069] ④ Take out the capillary and soak it with kerosene for 2 minutes to clean the asphalt deposited on the inner and outer walls of the capillary, so as not to affect the observation; blow dry the kerosene outside the tube with nitrogen, place it in a closed environment at 60℃ to dry, and obtain the oil-wet capillary, which is stored for later use.

[0070] (2) Test sample preparation

[0071] ① Use simulated seawater to prepare 0.3% test solution, and dye it with scarlet pigment, keep the solution temperature at 25±0.2℃, pour the test solution into the cuvette, and place the ruler close to the back wall;

[0072] ② Place the three processed capillaries vertically in the cuvette, keep the inclination angle of all the test capillaries consistent, and record the liquid level height before the capillary is immersed in the liquid and the liquid level height 10 minutes after it is immersed in the liquid. The difference between the two is the capillary self-absorption height, and the arithmetic mean is taken as the measurement result. The test results are shown in Table 2 below.

[0073] Table 2 Capillary self-priming height test results

[0074]

[0075]

[0076] It can be seen from the data in Table 2 that the capillary self-imbibition height of the nanofluid containing only surfactant is the lowest, while the capillary self-imbibition height of the nanofluid added with amphiphilic nanoparticles is improved by 26% to 59%.

[0077] Example 6: Experiment on evaluation of absorption efficiency

[0078] (1) Core preparation: The experimental cores were drilled and dried, and the gas permeability and porosity were measured. All experimental cores were evacuated and saturated with simulated formation water, and a constant pressure and constant speed pump was used to displace more than 5 PV to measure the water phase permeability. Then, oil-displacing water was performed to displace the experimental cores to the state of bound water, the volume of water displaced was recorded, and the oil phase permeability under bound water was measured.

[0079] (2) Place the experimental core into the self-priming instrument containing the sample to be tested, allow the core to self-prime and discharge oil, and record the amount of oil discharged over time; when the volume of discharged oil does not change for 72 hours, record the total volume of discharged oil and calculate the self-priming efficiency. The results are shown in Table 3 below.

[0080] Table 3 Imbibition oil recovery efficiency of different systems

[0081] system Imbibition oil recovery efficiency / % Example 1 42.28 Example 2 44.25 Example 3 38.29 Comparative Example 1 19.26 Comparative Example 2 21.24 Comparative Example 3 29.67 Comparative Example 4 35.74

[0082] It can be seen from the data in Table 3 that the nanofluids with added Gemini surfactants having surface active effects have stronger absorption capacity, which is 8-23% higher than the absorption efficiency of nanofluids without added Gemini surfactants having surface active effects. For nanofluids containing amphiphilic nanoparticles, with the increase of the concentration of amphiphilic nanoparticles, the absorption efficiency shows a trend of first increasing and then decreasing, and when the concentration is 0.1%, the absorption efficiency is the lowest. The higher the concentration, the easier it is for the nanoparticles to aggregate, the larger the particle size, the worse the activity, and the effect of stripping oil from the surface of the porous medium is weakened.

[0083] The above examples are merely illustrative of the present invention and do not constitute a limitation on the protection scope of the present invention. All designs that are the same or similar to the present invention fall within the protection scope of the present invention.

Claims

1. A nanofluid for oil drainage in low permeability reservoirs, the mass fraction composition of which is as follows: 0.01% to 0.03% of amphiphilic modified nano-SiO2 particles, 0.20% to 0.40% of Gemini surfactant, and the rest of the simulated seawater.

2. The nanofluid for oil drainage in low permeability reservoirs according to claim 1, characterized in that: The structure of the amphiphilic modified nano-SiO2 particles is as follows:

3. The nanofluid for oil drainage in low permeability reservoirs according to claim 2, characterized in that: The preparation method of the amphiphilic modified nano-SiO2 particles is as follows: S1, adding hydrophilic nano-SiO2 particles and solid paraffin to an aqueous solution of didodecyl dimethyl ammonium bromide, emulsifying and cooling to obtain paraffin microspheres; S2, adding the paraffin microspheres and 3-mercaptophenylpropyltriethoxysilane to ethanol and stirring, then adding hydrogen peroxide, continuing to stir and filter, and after removing the paraffin, obtaining nano-SiO2 particles functionalized with a portion of benzenesulfonic acid groups; S3, adding the nano-SiO2 particles functionalized with some benzenesulfonic acid groups into a solution of n-octyltriethoxysilane, and obtaining the amphiphilic modified nano-SiO2 particles through reaction.

4. The nanofluid for oil imbibition and drainage in low permeability reservoirs according to claim 3, characterized in that: In step S1, the mass ratio of the hydrophilic nano-SiO2 particles, the solid paraffin and the didodecyl dimethyl ammonium bromide is 1:5-24:0-0.25; In step S2, the mass ratio of the 3-mercaptophenylpropyltriethoxysilane to the paraffin microspheres is 1:1-10, and the stirring time after adding the hydrogen peroxide is 4-24 hours.

5. The nanofluid for oil imbibition and drainage in low permeability reservoirs according to claim 3 or 4, characterized in that: In step S3, the mass ratio of the n-octyltriethoxysilane to the partially benzenesulfonic acid functionalized nano-SiO2 particles is 1:0.8-3; The reaction temperature is 25-55°C and the reaction time is 4-6h.

6. The nanofluid for oil drainage in low permeability reservoirs according to any one of claims 1 to 5, characterized in that: The structural formula of the Gemini surfactant is as follows: The mineralization of the simulated seawater is 30000 mg / L to 50000 mg / L.

7. The method for preparing the nanofluid for oil drainage in low permeability reservoirs according to any one of claims 1 to 6, comprising the following steps: The gemini surfactant is added into the simulated seawater, and after being stirred evenly, the amphiphilic modified nano-SiO2 particles are added, and stirred evenly to obtain the mixture.